Effects of high intensity training and high volume training on endothelial microparticles and angiogenic growth factors - Wahl, P.; Jansen, F.; Achtzehn, S.; Schmitz, T.; Bloch, W.; Mester, J.; Werner, N. (PLOS ONE, 2014)
Endothelial microparticles (EMP) are complex vesicular structures shed from activated or apoptotic endothelial cells. As endurance exercise affects the endothelium, the objective of the study was to examine levels of EMP and angiogenic growth factors following different endurance exercise protocols.